Assessing entrepreneurial ecosystems' influence on green technology innovation: A cross-country analysis - Mohsen Khezri (Journal of Innovation & Knowledge (JIK), 2025)
This study explores the impacts of 11 diverse entrepreneurship indicators on green technology innovation (GTI) to determine the optimal environmental regulatory framework that fosters green entrepreneurship. Additionally, the study investigates the impacts of environmental regulations on GTI by utilizing nonlinear panel smooth threshold regression (PSTR) models on data collected from 18 countries from 2002 to 2020. By identifying a critical regulatory threshold of 1.89, the research reveals how varying levels of environmental regulations significantly influence GTI dynamics. The estimation results emphasize that GDP per capita and financial development are critical in fostering GTI. However, stringent environmental regulations can counteract these positive effects. Urbanization and trade openness also positively influence GTI, with environmental regulations complementing their impacts. The transition to a service-oriented industrial structure positively affects GTI. The results underscore the negative impact of entrepreneurship indicators, potentially diverting resources away from GTI. Nonetheless, environmental regulations with stringent enforcement mechanisms can counterbalance the negative impacts of specific entrepreneurship metrics. Among the entrepreneurship indicators analyzed, financing for entrepreneurs, governmental support and policies, and governmental programs exhibit an inverted U-shaped impact pattern, peaking at specific levels of environmental regulation.
Keywords: Q55; Q58; L26; O31; C23; 650; Entrepreneurial indicators; Environmental regulations; Green Technology Innovation; GTI; panel smooth threshold regression; PSTR